Safety and rapid response of dabrafenib and trametinib therapy during hyperbilirubinemia in metastatic melanoma - Shalata, Walid; Steckbeck, Rachel; Polishchuk, Ilya; Cohen, Ahron Yehonatan; Rouvinov, Keren; Tokar, Margarita; Abu Jama, Ashraf; Abu Saleh, Omar; Sheva, Kim; Yakobson, Alexander (Frontiers in Oncology, 2023)
This case report describes the occurrence of hyperbilirubinemia as a complication of metastatic melanoma. A 72-year-old male patient was diagnosed with BRAF V600E-mutated melanoma with metastases in the liver, lymph nodes, lungs, pancreas, and stomach. Due to a lack of clinical data and specific guidelines for the treatment of mutated metastatic melanoma patients with hyperbilirubinemia, a conference of specialists debated between initiating treatment or providing supportive care. Ultimately, the patient was started on the combination therapy of dabrafenib and trametinib. This treatment resulted in a significant therapeutic response via normalization of bilirubin levels and an impressive radiological response of metastases just one month post-treatment initiation.